(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Reduction of 2,3-trimethylenepyrido[2,3-d]pyrimidin-4-one by sodium borohydride was investigated in an alcohol solution. Selective reduction of only a N1=C2 double bound of the initial compound was shown. The isomeric 2,3-trimethylene-1,2,3,4-tetrahydropyrido[2,3-d]-pyrimidin-4-ones are formed and quantitatively separated on HPLC with chiral adsorbent column. Theoretically formation of four optical isomers of 2,3-trimethylene-1,2,3,4-tetrahydropyrido[2,3-d]pyrimidin-4-ones are discussed.